DESCRIPTION OF THE PSYCHOLOGY OF THE MILITARY IN THE NOVELS OF ABDURASHID NURMURADOV - Dilovar Nurmuradova Bokhadirovna (Galaxy International Interdisciplinary Research Journal, 2023)
In the article, the author managed to raise the description of an extremely complex personality of a person to the level of pathos, turning him into both a hero and a coward at the same time.Vahid, the hero of the work.He goes to war and comes back a completely different person. Vahid, who has become an evil man, after seeing death and killing people, understands that he cannot live without war in peacetime. When he learns of the enemy’s invasion of his country, he unwittingly returns to his evil state and gets rid of himself, dying in the war.